Seed Treatment With Jasmonic Acid and Methyl Jasmonate Induces Resistance to Insects but Reduces Plant Growth and Yield in Rice, Oryza sativa - Bhavanam, Santhi; Stout, Michael (Frontiers in Plant Science, 2021)
When applied exogenously to plants, jasmonates (i.e., jasmonic acid (JA) and methyl jasmonate (MeJA)) increase plant resistance against herbivores, and their use in pest management has been suggested. For integration into pest management programs, the benefits of the resistance induced by jasmonates must outweigh the costs of jasmonates on plant growth and yield. A previous field study in rice found that seed treatment with MeJA reduced densities of the rice water weevil, Lissorhoptrus oryzophilus, but also reduced plant growth. Yields from MeJA plots were similar to yields from control plots. Because this study was conducted under field conditions with natural levels of pest populations, it was unclear whether effects on growth and yield were due to direct effects of MeJA treatment on the plant or due to insufficient protection from rice water weevil feeding. Therefore, the present study was designed to characterize the effects of JA and MeJA seed treatment on rice plant growth and yield in a pest-free environment under greenhouse conditions. Seed treatment with 2.5mM JA and 2.5mM MeJA enhanced resistance in rice plants to rice water weevils when plants were exposed to weevils 30 days after planting. Seed treatment with MeJA reduced plant emergence and plant height at 4- and 14- days after planting, respectively, compared to JA and control treatments. However, numbers of tillers per plant at 45 days after planting and days to heading were unaffected by jasmonate seed treatment. Of four yield components (panicles per plant, filled grains per panicle, percent unfilled grains and filled grain mass) that were measured, only filled grain mass was reduced by seed treatment. Plants grown from MeJA-treated seeds showed 31% lower grain masses compared to plants grown from control-treated seeds. Thus, the effects of seed treatment with MeJA on plant growth were stronger immediately post-treatment and subsided over time, such that plant growth mostly recovered six weeks after treatment. At maturity, MeJA may reduce some but not all components of yield. Despite similar effects on rice water weevil resistance, the negative effects of JA seed treatment on plant growth and yield were smaller compared to MeJA seed treatment.